Enhancing Graduate Competitiveness Through PDCA-Driven Curriculum Management - Faradifa Evrillia Haniyan; Deti Rosdini (Journal of Innovation and Research in Primary Education, 2026)
Vocational education must respond dynamically to evolving industry demands through systematic curriculum management. The Plan-Do-Check-Act (PDCA) framework offers potential for continuous improvement, yet its application in resource-limited vocational schools remains underexplored. This qualitative case study examined PDCA implementation at SMK Mathla'ul Anwar Margahayu through in-depth interviews with school leaders (n=2), teachers (n=6), and industry partners (n=4), complemented by classroom observations and curriculum document analysis. Data were analyzed using Miles and Huberman's interactive model with triangulation ensuring trustworthiness. PDCA implementation demonstrated systematic improvements across all stages: industry-informed planning through structured stakeholder engagement, authentic implementation integrating Teaching Factory and Product-Based Learning (87.5% of lessons), reflective criteria-based evaluation with 78% of student products meeting industry standards, and evidence-based curriculum revisions. Five enabling factors emerged—visionary leadership, strategic partnerships, teacher professionalization, data-driven culture, and policy support—while four constraints were identified: infrastructure limitations, resource insufficiencies, teacher workload, and diverse industry requirements. Findings advance theoretical understanding by introducing "structured flexibility" in curriculum management, demonstrating how industrial quality frameworks adapt to educational contexts. PDCA proves effective when supported by enabling conditions, though sustainability requires systemic resource investment. The study offers replicable models for curriculum-industry collaboration applicable across diverse vocational education settings in the Industry 4.0 and Society 5.0 era.